DAMPAK KEBERADAAN RITEL MODERN TERHADAP KEBERLANGSUNGAN RITEL TRADISIONAL - ., Sahyunu; Manan, La Ode Abd.; ., Asbudin (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2020)
The purpose of this research is to find out if the are income differences, profit and number of buyers in traditional retail before and after the presence of modern retail. This research conducted in ranomeeto village in September 2019. This research quantitave approach with statistical analysis of paired sample t-test. The populations of this research were 34 traditional retail traders in ranomeeto village. Those sample were taken with saturation sampling. The data collection technique of this research used questionnaire and interview. Data analysis method of this research covering normality test then statistical analysis of paired sample t- test. Based on the result of paired sample t-test there is no significant difference toward income variable, profit and number of buyers before and after the presence of modern retail like indomaret.